Fabrication and characterization of microstacked PZT actuator for MEMS applications - Sabri, M.F.M.; Ono, T.; Said, S.M.; Kawai, Y.; Esashi, M. (2015)
A microstacked PZT actuator of dimensions 8 mmx 0.8 mm x 0.4 mm and capable of 2.3-mu m actuation under a voltage of 100 V was fabricated and characterized. This actuator was then integrated into a silicon microstage with dimensions of 20 mm x 20 mm x 0.4 mm requiring actuation by a miniaturized actuator. The microstage was designed containing a Moonie amplification mechanism in order to further amplify the actuation of the stacked PZT actuator. Experimental characterization of the microstage performance indicated that the combination of a stacked PZT actuator with the Moonie amplification mechanism was successful in enabling high amplification of the microstage to similar to 15 times the original displacement of the PZT actuator. A displacement of 16.5 mu m at an applied voltage of 60 V and a resonant frequency of 456 Hz in the lateral vibration mode was observed. The relationship between the actuator parameters and the microstage design and performance was also discussed in order to show that the customized fabrication of a miniature actuator was imperative for the successful design of a high area-efficiency microstage. Analytical derivation of the displacement of the stacked PZT actuator was also carried out in order to evaluate the effectiveness of the fabricated actuator compared with the ideal stacked PZT structure. 2013-0231